Reliability analysis for evaluation of factors affecting pollutant load reduction in urban stormwater BMP systems. (December 2015) - Park, Daeryong; Kang, Hyeongsik; Jung, Sang Hwa; Roesner, Larry A.
Abstract: Detention basins are used in best management practices (BMPs) of urban stormwater systems, and total suspended solids (TSS) are used as an indicator of urban nonpoint-source pollutant. To characterize the uncertainty of BMP effluent loads resulting from uncertainty in BMP performance models, this study incorporated uncertainty analysis into a model that predicts the performance of stormwater BMPs based on watershed imperviousness, BMP volume, and BMP surface area. The objective of this study was to examine an approach to urban stormwater BMPs for use in performance analyses. The k -C* model, which incorporates uncertainty analysis, was applied to the uncertainty of stormwater effluent concentrations in urban stormwater systems. To characterize the uncertainty of BMP effluent loads, frequency analysis of the runoff volume and BMP overflow was done, and the load frequency curve (LFC) was simulated with and without BMP conditions, and then verified using the observed TSS load. Finally, the effects of watershed imperviousness, BMP volume, and BMP surface area were investigated using reliability analysis. The results of this study could be used to estimate the appropriate BMP size to achieve a specific watershed-runoff-pollutant load. They could also be used to produce appropriate BMPs to meet the defined nonpoint-source pollutant regulations, including the total maximum daily load. Highlights: The load frequency curve and uncertainty analysis used to evaluate the TSS load reduction were verified. A load-resistance analysis was applied to compute the magnitude of different load frequency curves. The reduction of TSS based on BMP geometry and watershed imperviousness was estimated. An appropriate BMP surface area and volume to reach a target TSS load based on the watershed imperviousness can be suggested.